The Skewed Global Landscape of Higher Education Training and Research - Rumbley, Laura E. (International Higher Education, 2015)
Around the world, the number of both research centers/institutes focused on matters of higher education and degree-granting programs in the field of higher education, is growing. However, the expanding quantitative picture masks many unanswered questions about the content and quality of these activities. Furthermore, the concentration of centers and programs in a small number of wealthy countries presents a stark geographic divide between those with access to research and training relevant to the increasingly important field of higher education, and those without.